PENGARUH IKLIM ORGANISASI DAN SEMANGAT KERJA TERHADAP KINERJA PEGAWAI DI KANTOR CAMAT LAHUSA KABUPATEN NIAS SELATAN - Damai Telaumbanua (Jurnal Ilmiah Mahasiswa Nias Selatan, 2023)
The purpose of this study was to determine the influence of organizational climate and morale on employee performance at the Lahusa Sub-district Office, South Nias Regency. The type of research used is a quantitative type of causal nature. The source of the data was from employees, 0population and sample in this study being 31 people. Data collection techniques are research instruments or questionnaires. The data analysis method used is multiple linear regression analysis. The results of this study showed that the Fhitung value was 27,518>Ftabel 3,343. This research can be concluded that the organizational climate and morale have a significant simultaneous effect on the performance of employees at the Lahusa Sub-district Office, South Nias Regency. The suggestions in this study are (1) To increase employee work productivity, there are times when organizations always pay attention to the employee's work environment. (2) In achieving organizational goals to increase employee work productivity, it is better for work leaders and colleagues to motivate each other in completing office tasks